Animal and human health in the Sahrawi refugee camps - Angeloni, G; Carr, J (Refugee Studies Centre, University of Oxford, 2018)
Health challenges in the Sahrawi refugee camps in the Algerian desert are faced by both human and animal populations, and therefore responses must function for the benefit of both.